Software measurement : establish, extract, evaluate, execute - Ebert, Christof; Dumke, Reiner (Springer, 2007)
This comprehensive introduction to software measurement offers detail knowledge and experiences about the subject in an easily understood, hands-on presentation. It also provides guidance to all relevant measurement tools and online references.